SPINNING EXERCISE INTENSITAS SEDANG MENURUNKAN GEJALA DISMENORE PRIMER MAHASISWI DIII KEBIDANAN - Oktafiani, Hani; Susiarno, Hadi; Murniarti, Vita (Universitas Tribhuwana Tunggadewi, 2020)
Some young women including female students in Indonesia are still not free from complaints of dysmenorrhea syndrome. One of the effects of dysmenorrhea is a decrease in learning concentration and daily productivity. Activity that can be pursued is to change lifestyles to be more active in physical exercise, one of which is exercise training. The purpose of this study was to analyze the effect of moderate-intensity spinning exercise on reducing the symptoms of primary dysmenorrhea pain in female college students. This quantitative research uses a quasi-experimental design pre-test post-test design. Studies subjects numbered 32 where the control and intervention groups each consisted of 16 respondents. The intervention that will be given to the intervention group is a moderate intensity spinning exercise for 3 weeks with the FITT principle. The research data were analyzed by Mann Whitney and Wilcoxon statistical tests. The results of the analysis showed a decrease in dysmenorrhea pain symptoms before the intervention there was no significant difference (p> 0.05), whereas after the administration of the intervention showed there were significant differences in the intervention and control groups with a value of p = 0.001. The influence of moderate-intensity spinning exercise can reduce the symptoms of dysmenorrhea pain by 66%. Educational institutions can implement policies on the use of spinning tools in the environment of students and educate these tools to adolescents in the target area given their effective use to reduce menstrual pain.